Análise histológica e imunoistoquímica do tecido pulpar de ratos Wistar submetidos a procedimento clareador com duas concentrações de peróxido de hidrogênio - Benetti, Francine [UNESP] (2015)
Studies have shown damage to tooth pulp, and your capacity of tissue repair, after dental bleaching. This study investigated the necrosis process, the level of cell proliferation (immunolabeling with PCNA) and apoptosis (Caspase-3, cleaved), and inflammatory response (IL-17, IL-6 and CD5) generated in the pulp tissue after this procedure. Wistar rats were divided into Control (placebo gel), BLUE (20% H2O2,1x50min), and MAXX (35% H2O2, 3x15min) groups. At 2 and 30 days, the rats were killed (n=10).The jaws were removed and processed for histology analysis (H&E) and immunohistochemistry. Statistical tests were performed for each case, considering p<0.05. At two days, necrosis was observed on the occlusal third MAXX group and moderate inflammatory infiltrate in BLUE (p<0.05). At 30 days, there was no inflammatory infiltrate in groups, and large area of the pulp chamber was occupied by tertiary dentin. The immunolabeling for PCNA, at two days, was more expressive in the middle third of the BLUE group (p<0.05) and the cervical third of the MAXX (p<0.05), with significant reduction to 30 days in the cervical third (p<0.05). Caspase-3-cleaved was present in all groups, showing a higher level of apoptosis in the bleached groups compared with the control in both analysis periods (p<0.05); comparing the groups at 2 and 30 days, significant reduction in the level of apoptosis was observed only in BLUE group (p<0.05). CD5 positive cells were found in all groups in both analysis periods; at two days, the BLUE group had higher immunolabeling for CD5 in the occlusal third when compared to the other groups (p<0.05); in other thirds, both groups bleached showed most immunolabeling compared with the control group (p<0.05); there was no significant difference in the comparison of each group at 2 and 30 days (p>0.05). The MAXX group presented...